Standard deviation

σ = i = 1 n ( x i x ˉ ) 2 n \large \sigma = \sqrt{\dfrac{\sum_{i=1}^{n}(x_{i}-\bar{x})^2}{n}}

Consider the formula of standard deviation σ \sigma above. Given that the standard deviation σ a \sigma_a of elements of { a n } : a 1 , a 2 , a 3 , , a 2017 \{a_{n}\} : a_{1},a_{2},a_{3}, \ldots,a_{2017} is 2017 2017 . If elements of { b n } \{b_{n}\} is defined that b n = 2017 a n b_{n} = 2017 - a_{n} , find the standard deviation σ b \sigma_b of b 1 , b 2 , b 3 , , b 2017 b_{1},b_{2},b_{3} , \ldots,b_{2017} .

Notations : x ˉ \bar{x} denotes the data mean .


The answer is 2017.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Mar 14, 2017

Standard deviation σ \sigma is a measure of the spread of the data. By multiplying the data { a n } \{a_n\} by -1 and add 2017, just shifts the data laterally without changing the spread and hence the standard deviation remains the same. σ b = σ a = 2017 \implies \sigma_b = \sigma_a = \boxed{2017} .

Let us prove it as follows.

k = 1 n b k = k = 1 n ( N a n + 1 k ) = n N k = 1 n a k \begin{aligned} \sum_{k=1}^n b_k & = \sum_{k=1}^n \left(N - a_{n+1-k}\right) = nN - \sum_{k=1}^n a_k \end{aligned}

b ˉ = k = 1 n b k n = N k = 1 n a k n = N a ˉ \begin{aligned} \bar b & = \frac {\sum_{k=1}^n b_k} n = N - \frac {\sum_{k=1}^n a_k} n = N - \bar a \end{aligned}

Now, we have:

σ b = k = 1 n ( b k b ˉ ) 2 n = k = 1 n ( N a n + 1 k b ˉ ) 2 n = k = 1 n ( N a k N + a ˉ ) 2 n = k = 1 n ( a k + a ˉ ) 2 n = k = 1 n ( a k a ˉ ) 2 n = σ a \begin{aligned} \sigma_b & = \sqrt{\frac {\sum_{k=1}^n \left(b_k-\bar b \right)^2}n} \\ & = \sqrt{\frac {\sum_{k=1}^n \left(N - a_{n+1-k}-\bar b \right)^2}n} \\ & = \sqrt{\frac {\sum_{k=1}^n \left(N - a_k-N + \bar a \right)^2}n} \\ & = \sqrt{\frac {\sum_{k=1}^n \left(- a_k + \bar a \right)^2}n} \\ & = \sqrt{\frac {\sum_{k=1}^n \left(a_k - \bar a \right)^2}n} \\ & = \sigma_a & \blacksquare \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...